Application of RCPWAVE Model for morphological computation - Truong Ngoc Tuong; Suphat Vongvisessomjai; Tawatchai Tingsanchali; Tanaka, Hitoshi; Sutat Weesakul; DAAD (Bangkok : Asian Institute of Technology, 1993)
In order to compute the coastal morphology by Shoreline Model , the computations of wave field , longshore sediment transport and shoreline change are needed. In the computation of wave field , the RCPWAVE Model developed by Coastal Engineering Research Center (CERC) in 1986 and Time Dependent Mild Slope Model developed by Watanabe and Maruyama in 1984 are used and discussed . The inclusion ofreflection effect into RCPWAVE Model is made .The longshore sediment transport rates based on CERC 1975 , CERC 1984 and HANSON 1989 formulas are examined and applied. From variable wave data of many years , the new parameters (monthly and annual representative deepwater waves ) are introduced and used to compute shoreline evolution by two corresponding programs based on explicit scheme. These studies are applied to calculate the shoreline change in the western side of Map Ta Phut port. The comparison between computed and field results after two years is made . The obtained results confirm the capability of RCPWAVE model and the proposed method based on monthly and annual representative deepwater waves in morphological computation .
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering.
Keywords: Waves -- Mathematical models